Real time traveler information system : an efficient approach to minimize travel time using available media - Haque, Mohammad Mahmudul; Hasnat, Abul (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2005.